1992
DOI: 10.4141/cjps92-079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of varying seeding rates on hybrid and conventional summer rape performance in Manitoba

Abstract: To compare the effects of varying seeding rate on the agronomic performance, phenology and seed quality of hybrid and conventional summer rape cultivars. fbur hybrid and two conventional summer rape cultivars were seeded at 1.5,3.0,4.5,6.0 and 9.0 kg ha 'at two locations fbr 3 yr. The hybrid cultivars were, very imponantly .24vo hither yielding and pruluced 50% more toual dry manei than the ionventional cultivars.The hybrid cultivars were, on average, 1.3 % lower in seed oil content, 1.0% higher in seed protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
14
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 5 publications
10
14
0
Order By: Relevance
“…These results are in agreement with the findings of [5]- [7]. Humidity is low in mostly coastal area of the world and Temperature mostly range deviate very little from normal range in cropping season.…”
Section: Plant Height At Maturity (Cm)supporting
confidence: 83%
See 1 more Smart Citation
“…These results are in agreement with the findings of [5]- [7]. Humidity is low in mostly coastal area of the world and Temperature mostly range deviate very little from normal range in cropping season.…”
Section: Plant Height At Maturity (Cm)supporting
confidence: 83%
“…The data in (Table 1) shows C 2 produced maximum plant height as compared C 1 . Same results were reported by [5]- [9].…”
Section: Plant Height At Maturity (Cm)supporting
confidence: 77%
“…Essentially, such a situation could be expected. This finding agrees with that of Van Deynze et al (1992), who reported that increased row spacing delayed flowering in rape. In this study, days to flowering varied more than three days across the row spacings (15, 30 and 45 cm).…”
Section: Plant Growthsupporting
confidence: 83%
“…In contrast, the protein content was not affected by changes in plant density. This result concurs with the findings of Kondra (1977) and Van Deynze et al (1992), who reported that protein content did not change with varying plant densities. However, Shrief et al (1990) reported that protein content was higher under higher population densities.…”
Section: Seed Protein Contentsupporting
confidence: 80%
“…At these two sites, the lowest plant densities achieved were over 20 plants/m 2 . Similar responses to plant density have been reported by McGregor (1987), Van Deynze et al (1992) and Leach et al (1999). No interaction occurred between cultivar and sowing rate in three trials at Lameroo, indicating that cultivars with considerable differences in early vigour responded similarly to varying sowing rate.…”
Section: Grain Yieldsupporting
confidence: 80%